Peran Moderasi Usia Dalam Dukungan Sosial dan Kepemimpinan pada Anggota Organisasi Kemahasiswaan di Yogyakarta - Anggraeni, Dewi Soerna; Rinaldi, Martaria Rizky; Yuniasanti, Reny (Universitas Muhammadiyah Metro, 2023)
Indonesia Emas 2045 is a challenge for the younger generation to contribute as a future leader. Student organizations are one of the forums for building leadership in students. This study aims to determine the moderating role of age in social support and members of student organizations’ leadership in Yogyakarta. The subjects were 223 members of student organizations, a minimum of 2 months as a member. Sampling was gathered using the convenience sampling technique. Data collection was carried out using the Human Capital Sustainability Leadership (HSCL) scale and the Social Support Scale of the Online Community. Data analysis was conducted using Jamovi statistical software. The moderation analysis results showed that age significantly affects sustainability leadership (Estimation = 0.5814, SE = 0.24265, CI = [0.1059, 1.0570], Z = 2.40, p = 0.017). The older a person is, the higher the likelihood of having highly sustainable leadership. In addition, the interaction between social support and age also proved significant in sustainability leadership (Estimation = 0.0455, SE = 0.00495, CI = [0.0358, 0.0552], Z = 9.20, p < 0.001). That is, the effect of social support on sustainability leadership differs at different levels of individual age.